Caractérisation hydrologique et morpho-sédimentaire d’une zone de dragage en lagune Ebrié et risques de contamination de la nappe d’Abidjan : cas du secteur lagunaire Abatta- Bingerville (International Journal of Scientific Research and Management (IJSRM), 2020)
The main objective of this study is to assess the impacts of dredging on the Abidjan aquifer in the Bingerville sector. The data acquisition campaigns take place in July 2019. They consisted in the collection of morphobathymetric, hydrological and sedimentological data in the study area where catchment fields are located at most four (4) kilometers away. The physicochemical and microbiological analysis of the waters in this sector of the Ebrié lagoon has shown that they are of poor quality and therefore unsuitable for all domestic and consumer uses. Thus, any intrusion into the Abidjan aquifer would be synonymous with pollution of the aquifer water, the treatment of which would prove to be very expensive. The conductivity levels, especially at the bottom of the water (≥ 4m deep), are therefore higher than the WHO potability standard (2006) which is <2500 µS / cm. In addition, the bathymetric surveys obtained have highlighted topographic backgrounds with depressions of 4 to 5 m in general. However in dredging areas depths of more than 15 m have been observed. To assess the speed of sedimentation in order to assess the sanding capacity of dredged areas, this bathymetric map was superimposed on that of 1975 produced by TASTET. This superimposition highlights sedimentary movements with very significant sedimentation rates ranging from 1.7 to 1.9 m / s.